Full length histone H3 conjugated electrochemical biosensor for extracellular proteolytic Cathepsin L activity detection - Seong, Tae Wha; Seo, Jungmok; Lee, Kwan Hyi (ELSEVIER SCIENCE SA, 2018)
Timely and accurate detection of proteolytic extracellular Cathepsin L (CTSL) activity is vital for assessing the metastatic potential of cancer. In this article, extracellular CTSL activity was detected using biotinylated full length histone H3 (BFLH3) treated extended gate (EG) field effect transistors (FETs) with 104 times the sensitivity of fluorometric CTSL activity assays. Upon active reaction by CTSL, the treated BFLH3 is cleaved after amino acid 21, inducing a significant charge change on the EG surface due to the large size and charge of the cleaved BFLH3. This change in EG surface charge can be detected by FET, enabling the quantification of proteolytic extracellular CTSL activity. Moreover, self-normalized quantification of CTSL activity was achieved in heterogeneous LNCaP and PANC-1 cultured cell media, which accurately represented higher CTSL levels in LNCaP derived from metastatic lesion of human prostatic adenocarcinoma. CTSL activity detection with EG FET allows multiple measurements of CTSL activity with one FET and opens up the possibility of detecting other proteolytic enzymes for cancer diagnosis and prognosis. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: PROSTATE-CANCER; OVEREXPRESSION; METASTASIS; EXPRESSION; CARCINOMA; MARKER; CELLS